Sombra Projetada - Miranda Júnior, Edmilson Forte (2013)
Projected Shadow is the first stage of a game. It is a interactive installation whose creation – an artistic process of research and execution – proposes a vision about an institutional space as a place where power is exercised. The purpose is to expose the process logic. To reveal the game. An interactive video projection works as a meta-dispositif to talk about the dispositif according to Michel Foucault. A concept that is discussed in a dialog with the “liberating” possibilities inherent to the “universe of technical images” presented in part of Vilém Flusser’s work. In this context the artist-researcher proposes a work that, through metaphor and the artistic procedure, invests on itself. The system created to the work proposes the initial stage of a game that, supported by a set of planned rules, depends on public’s voluntary participation to happen. Sombra Projetada is the investigation on how a technical device can be used in order to promote experiences of creation and freedom.